Vibrational Spectroscopic Investigation of Ornidazole - An Antiprotozoan Agent - GUNASEKARAN, S.; ANITA, B. (Asian Journal of Chemistry, 2010)
In this work, a qualitative analysis of an anti-protozoan drug ornidazole, which belongs to the potent nitroimidazole category of drugs, has been carried out using FTIR and FT Raman spectroscopic techniques. A satisfactory vibrational band assignment of the drug has been made based on the postion, shape and relative intensity of the recorded spectra, in correlation with bands assigned in structurally related molecules. The stress degradation behaviour of the drug has been studied by employing FTIR spectroscopy.